The Prevention and Management of Community-Based Natural Disasters: through the "Kampung Tangguh" Concept in Sidorejo Village, Krian, Sidoarjo - Rachma, Siti Aldira (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2025)
The "Kampung Tangguh" concept, originally conceived as a response to the COVID-19 pandemic, has evolved into a multidimensional resilience model encompassing social, economic, and environmental aspects in Sidorejo Village. Therefore, this study focuses on how this communitybased initiative can be modified and strengthened to mitigate natural disasters. The research methodology employed a qualitative approach with a case study in Semampir Hamlet, Sidorejo Village, Krian District, Sidoarjo Regency. Data were collected through in-depth interviews with community leaders, village officials, volunteers, and residents, as well as through participant observation and document review. The results show that the “Kampung Tangguh” success in handling the pandemic, such as the formation of volunteer teams, the establishment of command posts, and an effective information system, has also increased economic value through agricultural and fisheries practices, particularly pomfret and paddy cultivation. These aquaculture and agriculture provide a strong foundation for adaptation to natural disasters. Active community participation in community service, preparedness training, and the utilization of local resources are key factors. However, challenges remain, such as a lack of formal funding and the need for more specific technical training. In conclusion, the "Kampung Tangguh" concept in Sidorejo Village, Krian District, Sidoarjo Regency, demonstrates that social capital and active community participation are key to building sustainable disaster resilience. This model serves not only as an emergency response mechanism but also as an education and empowerment platform that enhances community capacity to face future threats. This study recommends closer collaboration between the village government, relevant agencies, and the community to strengthen the technical capacity and sustainability of this program.